2009
DOI: 10.2486/indhealth.47.145
|View full text |Cite
|
Sign up to set email alerts
|

A Field Study to Determine the Effectiveness of Several Respiratory Protection Masks on the Styrene Exposure during Lamination Activities

Abstract: The use of styrene-containing resins in boatbuilding can be associated with increased external styrene exposure of the laminators. During the use of different types of respiratory protection masks it is shown that only the application of air purifying respirators leads to a significant reduction of the internal styrene body burden of 83% when worn during 72% of the total work time. In this way it is possible to comply with or to stay clearly below the biological limit value of 600 mg MA + PGA/g creatinine (BAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…We also found an overall inconsistency in work conditions and practices, which represents an important consideration for interpretation of styrene‐induced dyschromatopsia. For instance, proper PPE use and improvements in ventilation systems and other work practices have been linked to reduced styrene body burden. Divergence in these study characteristics may explain, to some degree, the reports of pronounced between‐study heterogeneity from earlier meta‐analyses .…”
Section: Discussionmentioning
confidence: 99%
“…We also found an overall inconsistency in work conditions and practices, which represents an important consideration for interpretation of styrene‐induced dyschromatopsia. For instance, proper PPE use and improvements in ventilation systems and other work practices have been linked to reduced styrene body burden. Divergence in these study characteristics may explain, to some degree, the reports of pronounced between‐study heterogeneity from earlier meta‐analyses .…”
Section: Discussionmentioning
confidence: 99%
“…The VOC reduction efficiency using half-type masks with an activated carbon filter was 26%, and that using a half-type respirator mask with an activated carbon filter was 83% [57]. The reduction efficiency of a half-type respirator mask with cartridges replaced once a day was 83.6% [58], and that of a half-type respirator mask with cartridges replaced once a month was 46.6% [58].…”
Section: Risk Reduction Scenariomentioning
confidence: 94%
“…Indirect evidence for effectiveness of PPE in preventing occupational asthma An updated review of the medical literature revealed indirect evidence that use of respiratory protective devices might prevent asthma onset, by demonstrating that respirators can reduce exposures to agents that can cause occupational asthma. These studies investigated: air purifying respirators [83] and half-face respirators with particulate/organic vapour/formaldehyde filters [84] used by firefighters; air purifying respirators [85], half-mask respirators with frequent cartridge changes [86], and half-face air purifying or full-face air-supplied respirators [87] for workers exposed to styrene; hood style supplied air respirators used to reduce exposure to chromium and other materials during sanding in aircraft manufacturing [88]; P2 facemasks and fresh-air helmets to reduce levels of rodent allergens among laboratory animal handlers [89]; and certified two-tie protective masks that reduced total particle concentrations by 97% in swine confinement buildings [90].…”
Section: Isocyanate Skin Exposure and Asthmamentioning
confidence: 99%